2009
DOI: 10.1007/s12664-009-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative chronotropic effect of proton pump inhibitors on frog-heart preparation

Abstract: Proton pump inhibitors (PPIs) have been known to cause bradycardia. We evaluated the effect of three PPIs, i.e. omeprazole, rabeprazole and pantoprazole on the heart rate of frog. The in situ frog heart preparation was set up. Heart rate and amplitude of contraction were studied following administration of different doses of the three PPIs. Statistical analysis was done by using Graphpad statistical software system. After 1 mg of omeprazole and rabeprazole, and 2 mg pantoprazole, the heart rate was similar as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A study evaluating animal model of frog by Gautam et al [ 28 ] , showed interesting results. They found that PPI in minimal used dose did not change heart rate, but when they increased doses twice, they noticed bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating animal model of frog by Gautam et al [ 28 ] , showed interesting results. They found that PPI in minimal used dose did not change heart rate, but when they increased doses twice, they noticed bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the heart, it has been shown previously that PPIs exert a strong negative inotropic effect on isolated ventricular myocytes as well as on isolated muscle strips of healthy rabbits , atrial muscle strips of patients undergoing cardiac surgery , and ventricular muscle strips of end‐stage failing human hearts . A negative chronotropic effect of PPIs has been demonstrated in isolated rat atrium and an in vitro preparation of a beating frog heart .…”
Section: Discussionmentioning
confidence: 97%
“…In vitro experiments have demonstrated a negative chronotropic effect in an isolated frog heart preparation and rat atrium . In addition, a negative inotropic effect of pantoprazole has been found in human and rabbit ventricular myocardium as well as human atrial myocardium .…”
Section: Introductionmentioning
confidence: 97%